Molecular epidemiological study of exosomes circZNF609, circPUM1, IGF2 with ischemic stroke - Suhai Fei; Miao Xu; ZhenFeng Liu; Haining Xie; Yue Yu; Yinghu Chu; Lijun Zhu; Zhengmei Fang; Yuelong Jin; Yingshui Yao; Yan Chen (BMC Cardiovascular Disorders)
Abstract Background Ischemic stroke (IS) is a common cardiovascular disease (CVD). Insulin-like growth factor 2 (IGF2), circZNF609, and circPUM1 are involved in metabolic regulation, vascular health, neuroprotection, and inflammation modulation and are relevant to IS mechanisms. This study investigated the effects of plasma exosomal expression of circZNF609, circPUM1, and IGF2 on IS. Methods The expression of circZNF609, circPUM1, and IGF2 mRNA in exosomes was detected in 145 patients with IS and 290 controls using real-time qPCR in a cross-sectional study. Q1–Q4 represents the quartile groups based on the target gene expression levels. Results There was no significant difference in the expression levels of circZNF609 and circPUM1 in the plasma exosomes between the IS and control groups (P > 0.05). However, a nonlinear relationship between the expression levels of circZNF609 in the IS group (P < 0.05). Exosomal IGF2 mRNA expression in the IS group was significantly lower than that in the control group (P = 0.043). The multifactorial adjusted results showed that in the case–control study of IS, circZNF609 in plasma exosomes was associated with a reduced risk of disease in group Q2 (adjusted OR: 0.565; P = 0.035) compared to that in group Q1, the low-expression group. In plasma exosomes, circZNF609 expression in group Q4 was associated with a reduced risk of disease in group Q1 (adjusted OR: 0.654; P = 0.004) compared to that in group Q1 (low expression). Plasma exosomes with IGF2 showed a reduced risk in the Q4 group with high IGF2 expression compared to that in the Q1 group with low IGF2 expression (adjusted OR: 0.543; P = 0.042). Conclusions This study suggests that the low expression of circZNF609, circPUM1, and IGF2 in peripheral blood plasma exosomes could pose a potential risk for IS and serve as biomarkers for clinical treatment.